‘What’s in a step if not a story?’ Cultivating Individual Interest and Engagement in Philippine Traditional Dance for Cultural Continuity: A Quasi-Experimental Study in Physical Education - Lobo, Joseph (Journal of Ethnic and Cultural Studies, 2026)
This quasi-experimental study examined how pedagogical framing influences students’ motivation and engagement in Philippine traditional dances. Ninety undergraduates enrolled in Physical Education (PATH-Fit 4: Philippine Traditional Dances) from a state university in the Philippines were purposively assigned into control (n = 45) and experimental (n = 45) groups. Both classes followed the full syllabus, which included orientation, classifications, fundamental steps, drills, practice and culminating performances of two major dances. The control group received conventional instruction that emphasized lectures, memorization and drills. The experimental group, while covering the same content, was taught using individual interest-based techniques such as icebreakers, storytelling, contextual framing and reflective questioning. Pre- and post-test surveys measured individual interest and study engagement. Independent samples t-tests confirmed baseline equivalence, and subsequent ANCOVA and 2 × 2 mixed-design ANOVA revealed significantly greater improvements for the experimental group. Findings suggest that individual interest-based techniques effectively foster lasting individual interest and sustained engagement, supporting cultural continuity through dance education.